“Where are the Botocudos?” Anthropological displays and the entanglements of staring, 1882-1883 - Georg Fischer (História, Ciências, Saúde: Manguinhos)
Abstract This article proposes an entangled perspective on nineteenth-century anthropological exhibitions. Whereas the existing scholarship mostly focuses on the receiving end of such displays or the agency of indigenous performers, this article argues for more stopovers and contextualization to grasp both the ambiguous position of non-metropolitan exhibitors like Brazil and the semantic transformations of traveling exhibits. In 1882, a group of Botocudo Amerindians was first taken to Rio de Janeiro and later put on display in Britain. Their presence in Rio sparked great interest, with lasting effects on the popular entertainment scene. Yet staring at them became a contested issue once they were taken to Europe, since Brazilians were concerned about becoming an object of Europe’s exoticizing voyeurism.